The Application of Digital Forensics in the Authentication and Admissibility of Electronic Evidence in Cybercrime Cases within the Jurisdiction of the Banda Aceh District Court - Puan Diva Humaira; Ida Keumala Jeumpa; Sanusi Sanusi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The legal status of electronic evidence is governed by Article 5, paragraphs (1) and (2) of the ITE Law. Electronic information and documents do not qualify as evidence by default; they must satisfy the formal and substantive criteria established by the ITE Law. Authentication and admissibility represent two interrelated phases in the evidentiary chain. Judicial practice exhibits variability in the evaluation of electronic evidence; some judges accept it without digital forensic investigation, whereas others require supplementary verification to ascertain its validity and integrity. This indicates that the problem resides in the fulfilment and evaluation of the criteria for authenticity and admissibility of evidence. This research aims to elucidate the role of digital forensics in the criminal justice system concerning the authenticity and admission criteria for electronic evidence in cybercrime cases at the Banda Aceh District Court. The employed research method is empirical legal research, which investigates societal, institutional, or state events and phenomena by direct observation. This research utilises both primary and secondary data sources. This research is conducted under the jurisdiction of the Banda Aceh District Court. This study involved the collecting, evaluation, and interpretation of data to elucidate the application of digital forensics in substantiating cybercrime. The research findings demonstrate that the implementation of digital forensics to fulfil the criteria of authentication and admissibility of electronic evidence in cybercrime cases at the Banda Aceh District Court has been executed during the investigation, prosecution, and trial phases within the criminal justice system. In terms of authentication, digital forensics is employed to verify the validity, integrity, and pertinence of electronic evidence related to the criminal incident under investigation. Digital forensics enhances the admissibility of electronic evidence through forensic examination reports and expert testimony that elucidate the technical validity and methodology of evidence acquisition.